EFFICACY OF NONINVASIVE DIAGNOSTICS OF ACUTE INFLAMMATORY RESPIRATORY DISEASES IN SCHOOL-AGE CHILDREN - Koloskova, О.К.; Bilous, Т.М.; Hnatiuk, М.G.; Kukhta, О.Y.; Bilous, V.V. (World of Medicine and Biology, 2018)
Objective: to improve the diagnostics of acute infectious-inflammatory respiratory diseases in school-age children by means of finding diagnostic value of certain noninvasive methods to examine patients. Materials and methods. 172 school-age patients were comprehensively examined and diagnosed with community-acquired uncomplicated pneumonia (І clinical group, 43 children), community-acquired pneumonia against the ground of bronchial-obstructive syndrome (ІІ clinical group, 19 school-children), acute or obstructive uncomplicated bronchitis (ІІІ group, 110 patients). The comprehensive examination of patients included cytological tests and microbiological inoculation of sputum, viral examination of swabs from the nasal pharynx, chest X-ray, C-reactive protein in the blood serum, biochemical examination of lung expiration condensate. Results and discussion. The results of microbiological examination of sputum taken from the patients of clinical groups were indicative of bacterial flora occurring in 83,9% of children from І group, 72,7% patients of ІІ group and 52,6% representatives of ІІІ group (р˂0,05 with І:ІІІ), fungal flora was found in 1,4% children of ІІІ group, and fungal-bacterial association in 9,7% patients of І group and19,7% of ІІІ group. It should be noted that pneumococcus was determined to be the most frequent causative agent, especially in association with Staphylococcus aureus (26,9%), and in the representatives from ІІ group – enterococcus (37,5%). The viral examination with negative results of bacteriological tests of sputum taken from patients of the clinical groups found respiratory-syncytial virus in all the patients from І group (100%), adenovirus in 33,3% of children and respiratory-syncytial virus in 66,7% from II group, in ІІІ group – adenovirus in 25,0% of patients, and respiratory-syncytial infection – in 55,0% of patients, their combination in 5,0% of cases and none of the agents – in 15,0% of examinations. The content of nitrogen monoxide metabolites in the lung expiration condensate of children from I and III clinical groups was practically similar: 35,4±7,02 and 39,3±3,63 micromole/L respectively, and in the representatives of II clinical group it appeared to be 1,5 higher and in an average was 52,3±7,51 micromole/L (P>0,05). The indices of the most optimal diagnostic value to determine infectious-inflammatory process of the lower respiratory tract were the markers of proteolytic activity by azoalbuminolysis higher than 1,4 ml/hour and azocasein more than 1,24 ml/hour. At the same time, C-reactive protein in the blood serum more than 24,0 mg/ml and nitrogen monoxide metabolites concentration in the lung expiration more than 45,0 micromole/L were associated with a probable risk of infectious-inflammatory process of the lower respiratory tract available. Conclusions: Routine diagnostic methods enable to verify severity of infectious-inflammatory process mainly but not its causes. High concentrations of C-reactive protein in the blood serum (more than 24,0 mg/ml) is the most specific although low sensitive in verification of pneumonic process, when the evidence of this process increases in 12 times as much. At the same time, satisfactory indices of sensitivity and specificity in detection of pneumonia belong to the markers of proteolytic activity by small and middle molecular proteinolysis in the lung expiration condensate, although they are not associated with statistically reliable risk of this inflammatory process of the alveolar part of the respiratory tract. The studies concerning optimization of diagnostic methods of acute respiratory pathology in children require further investigation on larger groups of patients with greater arsenal of noninvasive diagnostic procedures.
Keywords: children; diagnostic; respiratory diseases